Structural and magnetic investigations of a binuclear coordination compound of dysprosium(iii) dinitrobenzoate. Issue 12 (28th February 2019) - Sran, Balkaran Singh; Gonzalez, Jessica Flores; Montigaud, Vincent; Le Guennic, Boris; Pointillart, Fabrice; Cador, Olivier; Hundal, Geeta
Abstract : Dysprosium(iii ) dinitrobenzonate as a new single molecule magnet. Abstract : A centro-symmetric binuclear compound of formula [Dy(L )·(CH3 COO)2 ·(H2 O)2 ]2 (1 ) was isolated from the reaction between the 2, 4-dinitrobenzoate anion (L ) and the tris(acetate) of Dy(iii ). Single crystal diffraction studies reveal a μ1 –κ 2, η 1 :η 1 chelating binding mode ofL while the binuclear compound is formed by the two bridging (μ2 –κ 3, η 1 :η 2 ) acetate anions. The nona-coordinated sphere of each Dy(iii ) ion is filled with a chelating (κ 2, η 1 :η 1 ) acetate anion and two terminal water molecules. Static magnetic measurements combined with ab initio SA-CASSCF/RASSI-SO calculations lead to two intramolecular competitive interactions i.e. ferromagnetic exchange interactions (0.04 cm −1 ) and antiferromagnetic dipolar interactions (−0.5 cm −1 ). Finally, dynamic magnetic measurements revealed a Single-Molecule Magnet behaviour in a zero-applied magnetic field with an effective energy barrier Δ = 21.5(2) cm −1 and τ 0 = 7(3) × 10 −6 s through Orbach and Quantum Tunnelling of the Magnetization relaxation mechanisms.